MULTI – FACTOR AUTHENTICATION DALAM MENINGKATKAN KEAMANAN PERANGKAT IOT TERHADAP SERANGAN SIBER: SYSTEMATIC LITERATURE REVIEW - Hafidh Azizah (P3M Politeknik Negeri Banjarmasin, 2026)
Security aspects in the development and deployment of IoT devices are often crucial but overlooked. This is evident from the number of IoT devices that are faced with cyber threats due to suboptimal security systems. The reason for this problem is because during the development stage of IoT devices, some developers do not pay special attention to the implementation of strong security protocols. Based on these problems, this literature review aims to examine the extent to which Multi-Factor Authentication (MFA) can improve the security of IoT devices, especially in the face of increasingly complex cyber attacks. This literature review uses the Systematic Literature Review (SLR) method with the PRISMA framework approach to ensure a systematic and analytical review of related literature. Of the 155 journals traced with a time span of 2010 - 2024, 21 journals were obtained that met the predetermined eligibility criteria. Based on the results of the literature review, the implementation of Multi-Factor Authentication (MFA) on Internet of Things (IoT) devices is considered capable of mitigating and handling several security attack threats such as brute force attacks, Man-in-the-Middle (MITM), insider attacks, replay attacks, and other attacks.